Influence of the Mixing Grid Position on the Coolant Flow at the Outflow Part of the Nuclear Reactor Fuel Assembly Physical Model and Validation of CFD Model - Frantisek Urban; Lubor Kucak; Jozef Bereznai; Marian Pulmann; Jozef Tihanyi (Communications - Scientific letters of the University of Zilina, 2012)
In the year 2007 an experimental device with a physical model of the VVER 440 nuclear reactor fuel assembly was installed in the laboratory of The Institute of Power Engineering of the Faculty of Mechanical Engineering of the Slovak University of Technology in Bratislava. Within the framework of the reconstruction a third measuring plane was added to the original two, new combined probes were designed with temperature resistant sensors instead of the thermocouples, and piezoelectric pressure sensors for each probe were used. In this article we investigate the influence the mixing grid positioning has on smoothing the temperature profile in the fuel assembly outlet. The preliminary results of the ongoing validation of CFD simulations by means of experimental data are presented.